The executive's guide to enterprise social media strategy : how social networks are radically transforming your business - Thomas, David B., 1952-; Barlow, Mike. (Hoboken, N.J. : Wiley, 2011)
"An actionable framework for developing and executing successful social media strategies supporting collaboration, teamwork and communication in modern corporations Using straightforward language, this book offers real-world stories and revealing anecdotes to demonstrate how executives and business leaders develop successful corporate social media strategies. High level guidance to developing the practical business frameworks and policies necessary for implementing and managing successful corporate social media strategies Describes the actual processes, organizational structures, and technology platforms required to develop and execute a strategy of continuous engagement with customers, partners, and stakeholders Provides both how-to advice as well as best practices on creating an enterprise social networking strategy Other titles by Barlow: Partnering with the CIO: The Future of IT Sales Seen Though the Eyes of Decision Makers An executive handbook and referencefor social media strategy planning and development, The Executive's Guide to Enterprise Social Media Strategy answers all the questions you have on this topic, including why every corporation needs a social media strategy and how it can be successfully leveraged to achieve business objectives."--
The Executive's Guide to Enterprise Social Media Strategy; Contents; Foreword; Preface; Acknowledgments; Introduction; COUNTRY VILLAGE OR GLEAMING CITY?; BEYOND DISRUPTIVE; STEP ASIDE, FRED TAYLOR . . .; SOCIAL MEDIA OR WHAT?; WHY NOW?; SO, WHAT'S THE BEST WAY TO SKIN A MASTODON?; QUESTIONS YOU SHOULD BE PREPARED TO ANSWER; CRITICAL AREAS FOR SUCCESS; PART I: The Grand Scheme of Things; CHAPTER 1: Speed, Scope, Complexity, Power, and Potential; CHAPTER 2: The New Mode of Production; CHAPTER 3: The Social Enterprise; Part II: Building a Structure for Success.
Print version record.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Business enterprises -- Computer networks; Strategic planning -- Computer networks; Social media -- Economic aspects; Online social networks -- Economic aspects; Entreprises; x; x; x; COMPUTERS -- Internet -- Web Page Design; COMPUTERS -- Interactive & Multimedia; Business enterprises -- Computer networks; Online social networks -- Economic aspects; Social media -- Economic aspects; Strategic planning -- Computer networks; Business enterprises -- Computer networks; Social media -- Economic aspects; Unternehmen; Online-Marketing; Soziale Software; Gestion d'entreprise -- 2; Entreprises -- 2; Nonfiction